Protective effect of erythropoietin on post-MI liver tissue - KAYA, ÖZLEM TUĞÇE; ERCAN, FERİHA (My University, 2022)
Aim: Cardiac hepatopathy arises due to heart failure and influences has effects on heart recovery after myocardial infarction (MI).The aim of this study was to investigate the protective effect of Erythropoietin (EPO) on liver tissue exposed to ischemia due to MI. Material and Methods: Experimental MI was established by left anterior descending coronary artery ligation (CAL) and EPO or saline was injected immediately after CAL to five groups of rats, which groups are Control, Saline, EPO 5000, EPO 10000, CAL+1h. CAL+1h group was sacrificed one hour after CAL without any treatment. Other groups were sacrificed six hours after the operation. Liver tissues were examined histopathologically by Hematoxylin Eosin (HE) staining and electron microscopy. Results: Degenerative changes in liver tissue such as vacuolization, sinusoidal dilatation, hepatocyte pyknosis, Kuppfer cell activation were observed. Vacuolization, and sinusoidal dilatation increased in the Saline group compared to the control group (p=0.010 for both). Degenerated hepatocytes with pyknotic nuclei as well as activated Kuppfer cells were decreased in the EPO 10000 group compared to the Saline group (p=0.009), and activated Kupfer cells were decreased compared to the Saline and CAL+1h groups (p=0.035 and p=0.019, respectively). Conclusion: EPO protected liver tissue from histopathological damages regardless of dose, when given at the time of MI. EPO, when given immediately after MI, protected liver tissue from histopathological damage regardless of dose. Considering the mutual interaction of liver and heart, applying EPO to MI patients at first sight may prevent post-MI liver damage and contribute to the recovery of the heart.

Amaç: Kardiyak hepatopati, kalp yetmezliğine bağlı olarak ortaya çıkar ve miyokard infarktüsü (MI) sonrası kalbin iyileşmesini etkiler. kalp dokusu iyileşmesi üzerinde etkileri bulunmaktadır. Bu çalışmanın amacı, MI nedeniyle iskemiye maruz kalan karaciğer dokusu üzerinde Eritropoetinin (EPO) koruyucu etkisinin araştırılmasıdır. Gereç ve Yöntemler: Sol ön inen koroner arter ligasyonu (KAL) ile deneysel MI oluşturuldu ve Kontrol, SF (serum fizyolojik), EPO 5000, EPO 10000, KAL+1s. olmak üzere beş grup sıçana KAL'dan hemen sonra EPO veya SF enjekte edildi: KAL+1s grubu KAL'dan bir saat sonra herhangi bir tedavi uygulanmadan sakrifiye edildi. Diğer gruplar, operasyondan altı saat sonra sakrifiye edildi. Karaciğer dokuları Hematoksilen Eozin (HE) boyama ve elektron mikroskobu ile histopatolojik olarak incelendi. Bulgular: Karaciğer dokusunda vakuolizasyon, sinüzoidal dilatasyon, hepatosit piknozu, Kuppfer hücre aktivasyonu gibi dejeneratif değişiklikler gözlendi. SF grubunda vakuolizasyon ve sinüzoidal dilatasyon Kontrol grubuna göre arttı (her ikisi için p=0,010). EPO 10000 grubunda piknotik çekirdekli dejenere hepatositler SF grubuna göre azalırken (p=0,009), ve aktive Kuppfer hücreleri SF ve KAL+1s gruplarına göre azaldı (sırasıyla p=0,035 ve p=0,019). Sonuç: EPO, MI sırasında meydana gelmesinden hemen sonra verildiğinde, dozdan bağımsız olarak karaciğer dokusunu histopatolojik hasarlanmadan korumuştur. Karaciğer ve kalbin karşılıklı etkileşimi göz önüne alındığında, MI hastalarına ilk görüşte EPO uygulanması, MI sonrası karaciğer hasarını önleyebilir ve kalbin iyileşmesine katkıda bulunabilir.
Keywords: Kardiyak hepatopati; eritropoietin; iskemi; karaciğer; miyokard infarktüsü; Cardiac hepatopathy; erythropoietin; ischemia; liver; myocardial infarction